Fungsi Kartu Hijau (Izin) Untuk Meningkatkan Disiplin Siswa Dalam Proses Pembelajaran Di SMAN 3 Lengayang Kabupaten Pesisir Selatan - Wilis, Ratna; Melia, Yenni; Yasin, Faisal (Pendidikan Sosiologi, 2013)
Green Card function (Permit) To Improve Student Discipline In Learning Process SMAN 3 Lengayang Kab . South coast . In accordance with the above subject matter then dirumuskans research problem as follows : (1) How green card function (Permit) to improve student discipline in the Learning Process in SMAN 3 Lengayang South Coast . (2) Is the obstacles encountered by teachers in the implementation of a green card (Permit) to improve the learning process of students discipline.Â The approach used in this study is descriptive qualitative research type , where the approach intends to make a firm theoretical study and includes an explanation of the processes that occur in the local scope . Research informants taken by purposive sampling . Informants in this study consisted of 15 teachers , students of class XII 9 IPS1 , XII IPS2 and 5 people in the canteen owner SMAN 3 Lengayang South Coastal District . Type of data is divided into words and actions . The words and the person being observed or interviewed the main source . Techniques and data collection tools used were interviews , observation , documentation and data collection tools such as interview guides , books , pens and mobile phones .Â These results indicate that the green card (permit) cards used by SMAN 3 Lengayang can improve the discipline of students in the learning process of students who are often in and out of the classroom and students who often sat dikantin during the learning process can be reduced , the green card (permit) should only be used one student out of the classroom which in turn permit , the time given is only five minutes if it violates the existing laws of the teacher is sanctioned picket . However, in upholding the discipline of students there are some obstacles encountered by the teacher , the teacher is less compact run school rules that have been made with so still there are students who break the rules , there are some students who refused to sanction given by the teacher on duty , then the principal should be more mempertegaskan again to the teacher to follow the rules and regulations in accordance with the desired .